2014
DOI: 10.7860/jcdr/2014/8319.4758
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in Adolescents: have we Explored Enough! A Cross-sectional Study to Explore Adolescent Health in a City Slum in Northern India

Abstract: Context: Adolescent health is a relatively new focus area of India's National health program. However, little evidence is available for the existing problems especially in adolescent slum population. A study was planned to explore the problems of adolescent pertaining to sexuality, physical health, tobacco and alcohol use in slums of Urban Meerut, and create evidence base for informed planning and decision making by the local health authorities. Aims:To study the adolescent health in the slums of Meerut City, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
5
1
Order By: Relevance
“…Substance abuse was reported by 2.7% of the adolescents in this study, which is less as compared to the study by Jain et al in Meerut where 19% of the adolescents reported substance abuse. 15 In the present study, 0.6% of adolescents used smoked tobacco which is less compared to the study from Tamil Nadu which reported the prevalence of tobacco smoking among adolescents aged between 13-15 years as 5.3%. 17 Another study from Karnataka reported that 7.2% of adolescents in the age group of 15-19 years were tobacco smokers.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Substance abuse was reported by 2.7% of the adolescents in this study, which is less as compared to the study by Jain et al in Meerut where 19% of the adolescents reported substance abuse. 15 In the present study, 0.6% of adolescents used smoked tobacco which is less compared to the study from Tamil Nadu which reported the prevalence of tobacco smoking among adolescents aged between 13-15 years as 5.3%. 17 Another study from Karnataka reported that 7.2% of adolescents in the age group of 15-19 years were tobacco smokers.…”
Section: Discussioncontrasting
confidence: 74%
“…This finding is comparable to the study from Iran which reported the prevalence of hopelessness as 12.6%, butin contrast to the studies done in Meerut and Delhi which reported the prevalence of hopelessness among adolescents as 20.7%. [14][15][16] Substance abuse with tobacco and alcohol found to be less in this study population. Substance abuse was reported by 2.7% of the adolescents in this study, which is less as compared to the study by Jain et al in Meerut where 19% of the adolescents reported substance abuse.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Sexual issues are sensitive topics in Iran. As such, some parts of the questionnaire were identified as being culturally challenging by experts, however, their input led us to culturally adapt these sections to ensure that the questionnaire can be used in a sensitive and yet accurate manner not only in Iran but also in other countries where religiosity is a strong component of their cultures (13,14,17).…”
Section: Discussionmentioning
confidence: 99%
“…They did not perform the psychometric assessment of the questionnaire for age group 15-49 years (6). This instrument has also been used in other countries including India, Nepal, Ghana, Boamah, Saudi Arabia, Kenya Nigeriya, China and Tanzania, where religiosity is a strong component informing culture (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%